Experimental evaluation of the shore protection potential of the novel REEFS wave energy converter. (1st December 2020) - de Almeida, J.P.P.G. Lopes; Santos Martinho, M.F.E.
Abstract: REEFS is a novel multipurpose patented wave energy converter (WEC) that combines electric energy production with shore protection. The device shows some similarities with natural reefs and detached submerged breakwaters. However, unlike previous ones it is installed with an orthogonal alignment relative to coast line and with a greater freeboard. Exterior stay vanes, are another distinct characteristic of the device. Therefore, the REEFS differentiating functionality of shore protection cannot be directly extrapolated from detached submerged breakwater studies and the effective energy dissipation capacity of this new WEC taking into account its specific characteristics should be investigated. In this article an experimental investigation of the energy dissipation potential of REEFS WEC was implemented. A small scale physical model (1.5:100) was installed in a piston wavemaker flume and tested under regular wave conditions established by applying Froude similarity to typical West Portuguese sea state conditions. Resistive wave gauges were installed upstream and downstream the device, in order to record water level time series. Discrete Fourier transform technique was used to compute the wave energy spectra (WES). Energy dissipation was evaluated by comparing upstream and downstream WES. Two versions of the device were tested: i) without exterior stay vanes; ii) with exterior stay vanes. Regardless of the version, the REEFS model proved to be able to dissipate part of the incident wave energy. This capacity exhibited a dependence on the wave period, globally decreasing as the wave period increased. The version equipped with stay vanes always exhibited a substantially higher energy dissipation. From a relative point of view, stay vanes showed to be more important for long waves. REEFS energy dissipation was not far from the inferior values reported in literature review for submerged breakwaters of comparable dimensions, confirming the expectations about its shore protection functionality. Highlights: Quantitative evaluation of shore protection potential of REEFS new multipurpose WEC. Experimental set-up to evaluate wave energy dissipation by a submerged WEC. Impact of incident wave period in energy dissipation by the submerged REEFS WEC. Impact of exterior stay vanes in wave energy dissipation by the submerged REEFS WEC.